Digital Governance and Urban Government Service Spaces: Understanding Resident Interaction and Perception in Chinese Cities - Luhua Li; Xiaohong Lin; Xiaoting Yang; Zhiwei Luo; Min Wang (Land)
With the rapid development of smart cities and the swift transition toward digital governance, optimizing urban spatial governance through digital technology remains underexplored in the Global South, particularly from the perspective of resident perception and interaction. Digitization of government services is a key area of interest in digital governance research; this study investigates the impact of government self-service systems on the spatial perception and behavior of residents in Guangzhou and Foshan, China. Through a mixed-method approach, combining questionnaire surveys and semi-structured interviews and analyzing them using a structural equation model, the findings reveal that government self-service systems significantly influence residents’ spatial behavior and perception. These systems enhance the efficiency of administrative processes, increase convenience, and lead to temporal-spatial compression, thereby reshaping residents’ physical interactions with urban spaces. The findings provide practical insights for policymakers to enhance urban governance by integrating digital technologies to improve residents’ interaction with government services. These insights can guide the development of more efficient, resident-centered digital governance frameworks, particularly in rapidly urbanizing regions. This research contributes to a deeper understanding of how digital technology transforms urban spatial governance, highlighting the critical interplay between individuals, technology, and the urban environment. The study likewise provides examples of the ongoing digital transformation of public services in countries of the Global South that are lagging behind in the area of digital governance.